40th Anniversary of the Brazilian Journal of Biometrics - Canas Rodrigues, Paulo; Fernandes, Tales Jesus; Domingos Scalon, João; Malheiros, Euclides Braga (Brazilian Journal of Biometrics, 2022)
2022 marks the 40th anniversary of the Brazilian Journal of Biometrics. In honor of this occasion, the last issue of 2022 features invited contributions from our editorial board, along with a brief journal history.